HUBUNGAN BODY IMAGE DAN SIKAP TERHADAP MAKANAN DENGAN POLA MAKAN MAHASISWI JURUSAN GIZI POLITEKNIK - Abdurrachim, Rijanti; Meladista, Eka; Yanti, Rusmini (PERSATUAN AHLI GIZI INDONESIA, 2018)
The body image of a nutritionist will have an impact on the quality of health services for nutritionists by providing evidence and examples to patients. This study aims to find out the relationship between body image, and attitude towards food with dietary pattern of the students of Banjarmasin Health Polytechnic Department. This study design was cross-sectional. The study was conducted in April - May 2017 with a sample of 132 female students at level 1, 2 and 3. The sampling method was stratified random sampling. Data analysis used Spearman rank correlation test with α = 0.05. The results showed that 44.7 percent of students had a positive body image and a negative body image of 55.3 percent of female students. 46.2 percent of students had positive attitudes towards food and 53.8 percent had negative ones. As many as 59 percent had a good diet and 41 percent had a poor one. There was no relationship between body image and attitude towards food (p = 0.725), and there was a relationship between attitudes toward food and diet (p = 0.016). The conclusion of this study was that most Nutrition Department students had a good diet, negative attitudes toward food, and negative body image. The Nutrition Department was expected to be able to provide knowledge and socialization about body image to students by increasing the intake of vegetable, vegetable and fruit dishes per day as recommended, and applying a good diet.